Beyond monoamines: I. Novel targets and radiotracers for Positron emission tomography imaging in psychiatric disorders. Issue 3 (10th May 2022) - Lopresti, Brian J.; Royse, Sarah K.; Mathis, Chester A.; Tollefson, Savannah A.; Narendran, Rajesh
Abstract: With the emergence of positron emission tomography (PET) in the late 1970s, psychiatry had access to a tool capable of non‐invasive assessment of human brain function. Early applications in psychiatry focused on identifying characteristic brain blood flow and metabolic derangements using radiotracers such as [ 15 O]H2 O and [ 18 F]FDG. Despite the success of these techniques, it became apparent that more specific probes were needed to understand the neurochemical bases of psychiatric disorders. The first neurochemical PET imaging probes targeted sites of action of neuroleptic (dopamine D2 receptors) and psychoactive (serotonin receptors) drugs. Based on the centrality of monoamine dysfunction in psychiatric disorders and the measured success of monoamine‐enhancing drugs in treating them, the next 30 years witnessed the development of an armamentarium of PET radiopharmaceuticals and imaging methodologies for studying monoamines. Continued development of monoamine‐enhancing drugs over this time however was less successful, realizing only modest gains in efficacy and tolerability. As patent protection for many widely prescribed and profitable psychiatric drugs lapsed, drug development pipelines shifted away from monoamines in search of novel targets with the promises of improved efficacy, or abandoned altogether. Over this period, PET radiopharmaceutical development activities closely paralleled drug development priorities resulting in the development of new PET imaging agents for non‐monoamine targets. Part one of this review will briefly survey novel PET imaging targets with relevance to the field of psychiatry, which include the metabotropic glutamate receptor type 5 (mGluR5), purinergic P2 X7 receptor, type 1 cannabinoid receptor (CB1 ), phosphodiesterase 10A (PDE10A), and describe radiotracers developed for these and other targets that have matured to human subject investigations. Current limitations of the targets and techniques will also be discussed. Abstract : The emergence of positron emission tomography in the late 1970s facilitated non‐invasive assessments of brain function. In concert with conventional treatment approaches in psychiatry, positron emission tomography (PET) radiotracer development activities have historically emphasized monoaminergic targets, such as serotonin and dopamine receptors and transporters. More recently, psychiatric drug development priorities have shifted away from monoamines in search of novel targets offering improved efficacy and tolerability. This two‐part review surveys PET radiotracer developments paralleling major central nervous system (CNS) targets under investigation as novel treatment approaches for psychiatric disorders and applications thereof. Depicted are the primary cellular sources of these novel targets in the human brain. mGluR5, metabotropic glutamate receptor type 5, P2X7, purinergic P2X7 receptor; CB1, type‐1 cannabinoid receptor; PDE10A, phosphodiesterase 10A.